2012
DOI: 10.1007/s13365-012-0112-3
|View full text |Cite
|
Sign up to set email alerts
|

Survivin prevents apoptosis by binding to caspase-3 in astrocytes infected with the BeAn strain of Theiler’s murine encephalomyelitis virus

Abstract: This paper reports the upregulation of the gene coding for the apoptosis regulator family member "surviving" in SJL/J mouse brain astrocyte cultures infected with the BeAn strain of TMEV. cRNA from mock- and TMEV-infected SJL/J astrocytes was hybridised to an Affymetrix whole murine genome DNA microarray. Analysis revealed the upregulation of two sequences coding for the survivin protein in infected cells; this was confirmed by RT-PCR and qPCR. Western blotting showed an increase in the synthesis of survivin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Wee1 has been reported to inhibit CDK1 activity by phosphorylation (Chow and Poon, 2012;Magnussen et al, 2012), which in turn decreases survivin (Chen et al, 2013) and consequently activates Caspase-3 (Jones et al, 2010;Rubio et al, 2012). The phosphorylation of CDK1 and decrease in survivin are also involved in the mechanism of apoptosis via mitotic catastrophe (Castedo et al, 2004;Lamers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Wee1 has been reported to inhibit CDK1 activity by phosphorylation (Chow and Poon, 2012;Magnussen et al, 2012), which in turn decreases survivin (Chen et al, 2013) and consequently activates Caspase-3 (Jones et al, 2010;Rubio et al, 2012). The phosphorylation of CDK1 and decrease in survivin are also involved in the mechanism of apoptosis via mitotic catastrophe (Castedo et al, 2004;Lamers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interesting results were reported with the upregulation of survivin expression, where it formed a complex with the caspase-3 enzyme, nullifying the apoptotic events to be followed. 62 Supportive data also exist on the cytoprotective actions of dominant-negative survivin M34 against the DNA-damaging induced agents. 50,53 Given its protective potential, several mutant versions of wild-type survivin have been explored, of which the BIR-motif mutant known as dominant-negative survivin C84A was employed in this study.…”
Section: Proliferative Effects Of Surr9-c84amentioning
confidence: 98%
“…Previous studies found that Bcl-2 enhances the anti-apoptotic ability of the tumor cells by regulating the mitochondrial redox state of thiol ( 14 ). Survivin inhibits caspase activation, and therefore leads to the negative regulation of programmed cell death ( 15 ). In summary, these results show that the expression of anti-apoptotic associated genes, Bcl-2 and survivin , was extremely reduced following the silencing of Znf139 .…”
Section: Discussionmentioning
confidence: 99%